Combined effect of nutritional inflammation as well as depression on mortality in middle-aged and elderly people with osteoporosis and osteopenia - Yazhou Liu; Zhe Yang; Yuhao Li; Xiaodong Yang (PLoS ONE, 2025)
Background Inflammation, nutritional status, and depression interact complexly, impacting health outcomes. This study investigates their associations with all-cause and cardiovascular mortality in middle-aged and elderly individuals with osteoporosis. Methods Using NHANES data from 2007 to 2023, the study applied Cox regression models and restricted cubic spline plots to assess the effects of ALI (Advanced Lung Cancer Inflammation Index) and PHQ-9 scores on mortality outcomes in osteoporosis patients. Subgroup, threshold, and mediation analyses were also conducted. Results The study included 862 cases of all-cause mortality and 211 cardiovascular deaths. Higher ALI was associated with reduced mortality risk, while higher PHQ-9 scores indicated increased mortality risk. Combined analysis showed that osteoporosis patients with high ALI and no depressive symptoms had the lowest mortality risk. Restricted cubic spline and threshold analyses revealed a linear negative correlation between ALI and mortality risk and a nonlinear positive correlation between PHQ-9 scores and mortality risk. Subgroup analysis showed gender, physical activity, and sleep status influenced the interaction between ALI/PHQ-9 and mortality risk. Causal mediation analysis with bootstrapping found that ALI mediated 3.9% of the effect of osteoporosis on all-cause mortality and 5.6% on cardiovascular mortality, while PHQ-9 scores mediated 6.6% of cardiovascular mortality. Conclusion A significant negative correlation exists between ALI and mortality risk in osteoporosis patients, while PHQ-9 scores correlate positively. Favorable nutrition and inflammation, coupled with the absence of depression, help reduce mortality risks.